Prevalence and Risk of Carpal Tunnel Syndrome in Parkinson’s Disease: A Systematic Review and Meta-Analysis - Raafat, Kareem Wael; Amin, Ahmed M.; Ezz, Mohamed R.; Sabry, Ehab Naser; Ibrahim, Ismail A.; Attia, Amir N.; Mohammed, Mariam M. (MDPI, 2026)
Background: Parkinson's disease (PD) is a progressive neurodegenerative disorder characterised by motor and non-motor symptoms. Several studies have reported varying prevalence of Carpal Tunnel Syndrome (CTS) among individuals with PD. Objective: This study aimed to estimate the pooled prevalence of CTS in people with PD and explore any potential association between the two conditions. Methods: This systematic review and meta-analysis was conducted and reported in accordance with the PRISMA 2020 guidelines. A systematic search was performed across PubMed, the Cochrane Central Register of Controlled Trials (CENTRAL), Web of Science (WoS), Scopus, and EMBASE from inception to April 2024. Studies reporting CTS prevalence data in individuals with PD were included. Methodological quality was assessed using the National Institutes of Health (NIH) quality assessment tool. Pooled prevalence estimates were calculated using a random-effects model. Risk difference (RD) and risk ratio (RR) were calculated to assess the association between PD and CTS compared with control groups. Results: A total of 7 studies involving 411 participants (343 with PD and 68 controls) met the inclusion criteria, with 679 wrists assessed. The pooled prevalence of CTS in PD was estimated at 15% (95% CI: 0.07-0.28) with significant heterogeneity (p < 0.001, I-2 = 91%). The RD was 10% (95% CI: 0.04-0.16, p = 0.002), with low heterogeneity (p = 0.29, I-2 = 19%). The RR of CTS in PD compared with controls was 3.31 (95% CI: 0.60-18.42, p = 0.17), with moderate heterogeneity (p = 0.13, I-2 = 52%). Conclusions: This meta-analysis provides preliminary pooled estimates indicating a potentially increased prevalence of carpal tunnel syndrome in individuals with PD. Although the findings suggest a possible association, clinicians should maintain increased vigilance for CTS symptoms in patients with PD presenting with upper-limb sensory or motor complaints. From a biomechanical and functional perspective, these findings highlight the importance of routine upper-limb screening and the implementation of rehabilitation strategies targeting hand use, dexterity, and sensorimotor control within physiotherapy practice. Further high-quality studies with larger, well-characterised samples are required to confirm this relationship and clarify its clinical and functional implications.
Keywords: Carpal Tunnel Syndrome; Prevalence; Parkinson’s Disease; Entrapment Neuropathy